Diabetes mellitus Type 2 – the new face of an old lady (Swiss Medical Weekly, 2012)
Already 600 years before Christ, type 2 diabetes was known as a disease of elevated blood sugar levels associated with obesity. Since then, it appears, our understanding of the disease has not changed much, aside from the replacement of tasting the patients’ urine [1] by the measurement of plasma glucose and glycated haemoglobin levels (HbA1c) [2] for its diagnosis and the discovery of some new drugs. Already, in those old days a physician from India named Sushrut described diabetes mellitus as a disease characterised by the passage of large amounts of urine and its “honey-like” taste and, noteworthy, as a disease that is mainly associated with obesity and a sedentary lifestyle, recommending physical activity as the primary treatment option [3]. Although these milestone observations remain valid, major progress in the underlying pathogenesis of type 2 diabetes has been achieved showing a new face of this old disease and opening doors for novel treatment options. This review will highlight recent pathophysiological aspects of type 2 diabetes, actual diagnostic and treatment guidelines and discuss some possible upcoming new therapeutic strategies.